CO2 current efficiency in direct ethanol fuel cell - H. Hariyanto; Widodo W. Purwanto; Roekmijati W. Soemantojo (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2007)
In this present work, a systematically study on 20% PtCeO2/C catalyst for ethanol electro-oxidation in direct ethanol fuel cell were carried out. For cathode catalyst, a commercial catalyst of 40% Pt/C from ETEK was applied. Catalysts were printed on to carbon paper of TGPH 060 and sandwiched into membrane electrode assembly (MEA) and then arranged infitel cell with the geometric area 1.2 cm2. As an electrolyte, we used Nafion 117 from Du Pont. On-line Differential Electrochemical Mass Spectrometry (DEMS) measurement infuel cell setup was carried out in order to determine the activity and selectivity which was indicated by result of Faradaic current and CO2 current efficiency of ethanol electro-oxidation respectively. PtCeO2/C was significantly improving the selectivity of CO formation n comparison to the commercial catalyst of 20% Pt/C from A/fa Aesar- Johnson Mattews. Increasing of